Amino acids stimulate glycyl‐tRNA synthetase nuclear localization for mammalian target of rapamycin expression in bovine mammary epithelial cells. Issue 5 (23rd November 2018) - Yu, Mengmeng; Luo, Chaochao; Huang, Xin; Chen, Dongying; Li, Shanshan; Qi, Hao; Gao, Xuejun
Abstract: Amino acids are required for the activation of mammalian target of rapamycin (mTOR) to increase cell growth, protein and lipid synthesis, and inhibit autophagy. However, the mechanism through which amino acids activate the mTOR signaling is still largely unknown. In our previous study, we discovered that glycyl‐tRNA synthetase (GlyRS) is a key mediator of amino‐acid‐induced mTOR expression and activation in bovine mammary epithelial cells (BMECs). Here we show that amino acids stimulate GlyRS nuclear localization for mTOR expression in BMECs. Met stimulates GlyRS nuclear localization, and the nuclear GlyRS is cleaved into a C‐terminus‐containing truncated form. We prove that GlyRS has a bipartite nuclear leading sequences, and GlyRS is phosphorylated at Thr544 and Ser704 in the cytoplasm under the stimulation of amino acids (Met, Leu, and Lys). The nuclear GlyRS physically binds to nuclear factor kappa B1, triggers its phosphorylation, thereby enhancing mRNA expression of its target genes including mTOR, S6K1, and 4EBP1. We further demonstrate that GlyRS is required for the inhibition of autophagy by Met. Thus our work elucidates that amino acids trigger GlyRS phosphorylation and nuclear localization to enhance the mRNA expression of mTOR. Abstract : Glycyl‐tRNA synthetase (GlyRS) has a bipartite type of nuclear localization signals in its WHEP domain, and amino acids (Met, Leu, and Lys) trigger GlyRS phosphorylation at Thr544 and Ser704 in the cytoplasm and subsequent nuclear translocation. Nuclear p‐GlyRS physically interacts with and stimulates nuclear factor kappa B1 phosphorylation, thereby stimulating the expression of its downstream gene mammalian target of rapamycin and inhibiting autophagy.